2014
DOI: 10.1016/j.jcf.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values of antibodies against Pseudomonas aeruginosa in patients with cystic fibrosis one year after early eradication treatment

Abstract: Determination of serum antibodies against P. aeruginosa one year after first detection of P. aeruginosa and early eradication treatment can predict success of long-term eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…P. aeruginosa serology has proved a useful clinical tool in supporting clinical decision making [15,[17][18][19]. The principle has limitations [20,21], and treatment decisions should not be based on P. aeruginosa antibody levels alone, since the antibody response to some antigens may be delayed [17].…”
Section: Usefulness Of Risk Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…P. aeruginosa serology has proved a useful clinical tool in supporting clinical decision making [15,[17][18][19]. The principle has limitations [20,21], and treatment decisions should not be based on P. aeruginosa antibody levels alone, since the antibody response to some antigens may be delayed [17].…”
Section: Usefulness Of Risk Algorithmmentioning
confidence: 99%
“…Patients with CF are followed closely for their entire lives and there might be a benefit in using serodiagnosis as a complement to routine culture, in the same way that antibodies against Pseudomonas aeruginosa and Aspergillus are used successfully in many CF centres [15][16][17][18][19]. Limitations in the predictive values of such assays have been reported [20], and currently antibody measurements for P. aeruginosa are used clinically in combination with culture results, rather than as stand-alone tests [21].…”
Section: Introductionmentioning
confidence: 99%
“…A serological test could potentially guide disease management, a principle which is in use for other CF pathogens. [3][4][5][6][7][8] Relying on serology alone to diagnose chronic infection in CF is not sufficient, 9 but combining antibody measurements with culture results can yield simultaneously good sensitivity and specificity. 10 One approach is to comprehensively screen CF populations for antibodies and then reserve frequent sputum culturing for those, who are antibody positive.…”
Section: Introductionmentioning
confidence: 99%
“…There is no current gold standard regarding determination of successful eradication or how long a patient may remain free of Pa. In a retrospective study published in this issue of the Journal of Cystic Fibrosis Kappler et al [13] demonstrated that antibody testing one year after first Pa detection may predict long-term eradication outcome. They showed that the absence of antibodies on a single test one year after eradication therapy had a good predictive value for long-term eradication and might facilitate personalizing future eradication regimes.…”
Section: Can Serology Predict Long-term Eradication Outcome?mentioning
confidence: 99%
“…As many children with CF have their initial infection with Pa in very early life, the median age of acquisition reported in the AREST CF program was 26 months for children diagnosed following detection by newborn screening [6], an accurate indication of early infection would allow better targeted eradication therapy. One approach that has been suggested is measuring serum levels of anti-Pa antibodies and four articles in the Journal of Cystic Fibrosis have recently examined this topic [10][11][12][13]. Mauch and Levy [11] conducted a systematic review of the literature covering the last 40 years of research into the utility of measuring serum antibodies to Pa.…”
mentioning
confidence: 99%